Nutritional knowledge and practice among antiretroviral therapy user adults in Bule Hora hospital, southern Oromia, Ethiopia - Gemede, Habtamu Fekadu; Yazew, Tamiru (Frontiers in Nutrition, 2024)
Introduction Nutrition is the necessary basis for life, health, and human development over the entire lifespan. Poor nutritional knowledge, poor nutritional practices, and malnutrition among HIV-positive adults can contribute to accelerating the progression of Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS) and related diseases. Therefore, this study aimed to assess the dietary knowledge, practices and associated factors of HIV-positive adults participating in antiretroviral therapy (ART) at Bule Hora Hospital, West Guji Zone, South Oromia, Ethiopia. Methods A cross-sectional institutional study was conducted among 418 HIV-positive adults by systematic sampling technique. Semi-structured questionnaires were used for data collection and analyzed with SPSS version 21.0. Logistic regression analyses were used to identify factors associated with dependent variables using adjusted odds ratio (AOR), with 95% CI (confidence interval) at p < 0.05. Results The result of this study showed that the prevalence of poor nutritional knowledge and poor nutritional practices among (HIV) positive adults was 74.9 and 69.1%, respectively. In the multivariate analysis, adult age (AOR = 2.37, 95% CI: 1.30, 4.32), marital status (AOR = 2.46, 95% CI: 1.29, 4, 69), educational level (AOR = 1.83, 95% CI: 1.01, 3.30) and occupational status (AOR = 0.55, 95% CI: 0.25, 0.94) were significantly associated with the nutritional knowledge. Educational level (AOR = 2.58, 95% CI: 1.48, 4.50), monthly income (AOR = 2.80, 95% CI: 1.68, 4.69), and adult occupational status (AOR = 0.48, 95% CI: 0.26, 0.89) were also significantly associated with the level of dietary practice. Conclusion It was concluded that the respondents’ nutritional knowledge and practices in the city of Bule Hora were poor compared to other national findings. The identified factors related to nutritional knowledge and practices were educational level, monthly income, adult occupation, and marital status of respondents in the study area. Therefore, each concerned agency should address the above gaps in nutritional knowledge and practices of HIV-positive adults in the study area.